Trust-building vs. “just trust me”: reflexivity and resonance in ethnography - Pugh, Allison J.; Mosseri, Sarah (Frontiers in Sociology, 2023)
Amidst a perceived credibility crisis, recent scholarship has challenged basic norms of how ethnographies are conducted. This article identifies, underlying these critiques, a “trust me” fallacy that misunderstands ethnography as requiring blind trust in the researcher, leading to proposed reforms that promote extractive research practices by treating truths as raw commodities to be traded in for credibility. We argue such practices are unlikely to resolve critics’ concerns, and at the same time, they challenge the ethnographic capacity for resonance. Building on recent work in cultural sociology, we elaborate and refine a “textured model of resonance” to capture one of ethnography’s unique contributions: excavating ambivalence, plurality and complexity. We conclude by noting how time-honored practices of reflexivity, honed through productive dialogue among practitioners, address issues of trust and reliability without threatening what ethnography does well.